MOTIVATION OF USING FACEBOOK INFLUENCES INTERPERSONAL COMMUNICATION EFFECTIVENESS - Selfiana, Selfiana; Munadzdzofah, Ofah (Jurnal Administrasi dan Kesekretarisan, 2017)
Facebook is one of the social media that has been used by many people, ranging from children to adults. Based on the observation, the housewives tend to use facebook to communicate with various motivations. The messages written in the status of facebook influence the interpersonal communication effectiveness in the real world. This research used quantitative method. The result showed that the interpersonal communication effectiveness among housewives is quite influenced by the motivation of using facebook. This is indicated by the correlation coefficient value of 0,433. The result of determination coefficient 18,7% showed that the motivation of using facebook give the influence of 18,7% toward the interpersonal communication effectiveness among housewives in Cluster Ubud, Puri Gading Housing, Bekasi.